Impact of Particulate Matter Exposure and Aerobic Exercise on Circulating Biomarkers of Oxidative Stress, Antioxidant Status, and Inflammation in Young and Aged Mice - Su-Youn Cho; Hee-Tae Roh (Life, 2023)
Exposure to particulate matter (PM) and exercise training can have antagonistic effects on inflammatory responses and the balance between pro-oxidants and antioxidants in the body. However, the underlying mechanisms of these effects remain unclear. This study aimed to investigate the effects of PM exposure and aerobic exercise training on oxidative stress, antioxidant status, and inflammation in mice of different ages. Two groups of male C57BL/6 mice, comprising forty 1-month-old and forty 12-month-old mice, were exposed to either PM or exercise training or both for 8 weeks. PM exposure led to significantly higher 8-hydroxydeoxyguanosine (8-OHdG), malondialdehyde (MDA), interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor α (TNF-α) levels (p < 0.05) and significantly lower superoxide dismutase (SOD) and catalase (CAT) activities (p < 0.05) in both age groups exposed to PM compared to the control groups. Conversely, aerobic exercise training led to significantly lower 8-OHdG, MDA, IL-1β, IL-6, and TNF-α levels (p < 0.05) and significantly higher SOD and CAT activities (p < 0.05) in both age groups receiving exercise training, compared to those exposed to PM. Moreover, young mice in the exercise training and PM group showed significantly lower 8-OHdG, MDA, and IL-1β levels (p < 0.05) and significantly higher SOD and CAT activities (p < 0.05) than young mice in the PM exposure group. However, these levels did not vary significantly between the group of old mice that either received exercise training or exposure to PM. Our results suggest that while PM exposure could cause pro-oxidant/antioxidant imbalances and inflammatory responses, regular aerobic exercise could ameliorate these negative effects, although these vary with age. Nevertheless, the antioxidant and anti-inflammatory effects of exercise were countered by PM exposure, especially in older mice.